The quality and storage efficiency of some apple varieties as a function of picking date, area of production and duration of storage - Sass, P.; Lakner, Z. (International Journal of Horticultural Science, 1999)
Numerous apple varieties have been tested parallel with traditional Jonathan varieties during four years, 1990-1994 on three different geographical areas of Hungary. The picking time took place at three different times in a year: ten days before the probably optimal picking time, at close-to-optimal picking time, and ten days after the optimal picking time. The effect of storage on quality of fruits have been tested in February, March, and April under circumstances of a semi-industrial storage experiment. The results of experience can contribute to answer numerous current, from point of view of practice important topics: • The stochastic relations between various fruit quality parameters at different varieties • The change of fruit — quality during storage • The effect of different picking date on storage losses • The possibilities of storage — loss predicting by the utilization of multiple regression analysis. The most important results of experiences are as follows : • The starch — degradation test and Streiff — index are well applicable for practical purposes to determine the optimal harvest-date. • On base of analysis of various losses and physiological diseases the high importance of mass loss is obvious. In the variety Jonnee the earlier picking date considerably increased the mass loss. The effect of variety on mass loss is rather limited. In the Jonathan varieties the Jonathan spot was a rather important physiological disease. The late picking time increased the frequency of Jonathan - spot. At optimal date of harvest at Jonnee the frequency of Jonathan -spot was lower, than at Jonathan M 41. In the Jonathan M41 and Jonnee the importance of scald was rather limited, but in the Wellspur Delicious and Smoothee this disease occurred relatively frequently. In the Smoothee the earlier picking time considerably increased the probability of scald. • The multiple regression analysis yielded reliable results, fit for prediction of storage losses and diseases on the base of chemical and physical properties, determined at the time of picking.